Morbidity profile and anthropometry among the elderly in an urban slum in Mumbai - Thampi, Jerome G.; Hadaye, Rujuta (International Journal Of Community Medicine And Public Health, 2019)
Background: Geriatric health is gaining in urgency and importance as the world is moving into the later stages of the demographic cycle. Nutritional status of the elderly is a major determinant of their overall health. Methods: The present study is a healthcare facility-based, cross-sectional study among geriatric patients attending the chronic disease clinic focusing on the morbidity profile and anthropometry. Sample size was 89. The measurements done were calf circumference (CC), mid-upper arm circumference (MUAC) and BMI. Results: More than half the study subjects had three or more chronic morbidities. The prevalence of undernourishment based on calf circumference and MUAC were 11.2% and 12.4% respectively. The correlation between BMI, CC and MUAC were all found to be strong and statistically significant. Conclusions: Both CC and MUAC can be adapted for use in primary care settings to rapidly assess nutritional status of the elderly and plan management protocols.